2022
DOI: 10.3389/fmicb.2022.835950
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Supplementation With Fine-Grinding Wheat Bran Improves Lipid Metabolism and Inflammatory Response via Modulating the Gut Microbiota Structure in Pregnant Sow

Abstract: This study investigated the effects of fine-grinding wheat bran on pregnant sow body condition, lipid metabolism, inflammatory response, and gut microbiota. In this study, wheat bran was crushed into three particle sizes. A total of 60 Landrace × Yorkshire second parity sows were allotted to two groups: CWB (a diet containing coarse wheat bran with particle size of 605 μm) and FWB (a diet containing fine wheat bran with particle size of 438 μm). Fine-grinding wheat bran had higher soluble dietary fiber concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…The intestinal microbiota is closely associated with oxidative stress and inflammation and many exogenous additives regulate oxidative stress and inflammation levels in the body by modulating the structure of the intestinal microbiota [34,35]. Dietary fiber composition in the gestational diet of sows can modulate the antioxidant capacity and inflammatory responses of both the mother and offspring by regulating the composition of the intestinal microbiota [36].…”
Section: Discussionmentioning
confidence: 99%
“…The intestinal microbiota is closely associated with oxidative stress and inflammation and many exogenous additives regulate oxidative stress and inflammation levels in the body by modulating the structure of the intestinal microbiota [34,35]. Dietary fiber composition in the gestational diet of sows can modulate the antioxidant capacity and inflammatory responses of both the mother and offspring by regulating the composition of the intestinal microbiota [36].…”
Section: Discussionmentioning
confidence: 99%
“…Leptin is an appetite-suppressing hormone that is secreted after consuming diets and acts on the brain to induce satiety [47]. Sows fed high DF during gestation experienced decreased plasma leptin concentrations before farrowing, which negatively correlated with the feed intake of sows during lactation [43,48]. However, recent research has focused on the effect of long-term DF consumption on serum leptin levels compared to a control diet through a meta-analysis in humans.…”
Section: Effects On Endocrine and Metabolic Statusmentioning
confidence: 99%
“…These factors have been used as primary criteria to determine the immune status. The studies reported a positive response in immune status, suggesting that sows fed high DF generate more microbiota-derived SCFA that enhances the barrier function in intestinal epithelial cells [18,48,62]. Enhanced barrier function in the intestine decreases the gut permeability, which leads to the prevention of the inflow of endotoxins.…”
Section: Effects On Endocrine and Metabolic Statusmentioning
confidence: 99%
“…While small particles favor the families Ruminococcaceae and Porphyromonadaceae , medium particles favor the family Bacteroidaceae . Similar to maize bran, fine-ground wheat bran (FWB, 438 μm particle size) has higher soluble fiber, swelling capacity, water-holding capacity, and fermentability than coarse wheat bran (CWB, 605 μm particle size) [ 45 ]. When feeding pregnant sows, FWB resulted in a significantly increased abundance of Bacteroidetes and decreased abundance of Firmicutes at the phylum level.…”
Section: Foods and Nutrition On The Gut Microbiome And Intestinal Healthmentioning
confidence: 99%